2017
DOI: 10.1002/adhm.201701065
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Developing Injectable Matrices for Enhancing Cell Delivery and Tissue Regeneration

Abstract: Biomaterials are key factors in regenerative medicine. Matrices used for cell delivery are especially important, as they provide support to transplanted cells that is essential for promoting cell survival, retention, and desirable phenotypes. Injectable matrices have become promising and attractive due to their minimum invasiveness and ease of use. Conventional injectable matrices mostly use hydrogel precursor solutions that form solid, cell-laden hydrogel scaffolds in situ. However, these materials are associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
53
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 138 publications
(173 reference statements)
0
53
0
Order By: Relevance
“…Administrating cells through high‐gauge needles is becoming more common due to the development of cell therapies and 3D bioprinting technologies; however, previous studies have shown that injecting cells through clinically relevant needles often results in cell death and poor cell viability . Targeted cell delivery is often desired for medical application, but the therapeutic effect of the treatment is decreased because many of the cells injected in saline solutions (i.e., phosphate‐buffered saline [PBS]) are regurgitated due to the pressure in the tissue and fluid flow away from the injection site . Technology development is needed to enhance the delivery, protection, and encapsulation of cells to increase the viability and local retention of cells when injected.…”
Section: Rheological Properties Of Hpmc:np and Alginate Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Administrating cells through high‐gauge needles is becoming more common due to the development of cell therapies and 3D bioprinting technologies; however, previous studies have shown that injecting cells through clinically relevant needles often results in cell death and poor cell viability . Targeted cell delivery is often desired for medical application, but the therapeutic effect of the treatment is decreased because many of the cells injected in saline solutions (i.e., phosphate‐buffered saline [PBS]) are regurgitated due to the pressure in the tissue and fluid flow away from the injection site . Technology development is needed to enhance the delivery, protection, and encapsulation of cells to increase the viability and local retention of cells when injected.…”
Section: Rheological Properties Of Hpmc:np and Alginate Materialsmentioning
confidence: 99%
“…Technology development is needed to enhance the delivery, protection, and encapsulation of cells to increase the viability and local retention of cells when injected. Previous works have shown that hydrogels are promising alternatives to PBS for administration of cell therapies, as they enhance local retention and improve the viability of cells during injection when compared to injections performed in PBS . It has been proposed that hydrogel “plug flow,” a phenomena caused by the rheology of these materials, protects the cells from the shear and extensional forces during injection from a syringe and needle .…”
Section: Rheological Properties Of Hpmc:np and Alginate Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the biomaterial should provide suitable biophysical and biochemical microenvironmental cues for enhanced control of cell function in vivo . However, current injectable biomaterials suffer from ineffective modulation or lack of porosity for mass transport, cell motility, proliferation, cell–cell adhesion, or new tissue formation …”
mentioning
confidence: 99%